Workshop Teknologi Robotika untuk Anak Usia 8-15 Tahun di Kota Batam - Indra Hardian Mulyadi; Senanjung Prayoga; Rifqi Amalya Fatekha; Hendawan Soebhakti; Eko Rudiawan Jamzuri; Lindawani Siregar; Heru Wijanarko; Eka Mutia Lubis; Ika Karlina Laila Nur Suciningtyas; Vivin Oktowinandi; Ridwan Ridwan; Fitriyanti Nakul; Budi Sugandi (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2022)
The Covid-19 pandemic requires elementary and junior high school students to do online learning activities at home. In practice, children interact more often with their gadget during online school hours and outside these hours. Its a concern for most Graha Nusa Batam community residents because the children there are already starting to have symptoms of gadget addiction. Against this background, Batam State Polytechnic (Polibatam) held a robotics technology workshop program for children aged 8-15 years. This activity aims to increase children's understanding of robotics technology, which includes electronics and mechanics. In addition, this activity provides several benefits, namely: being an attractive alternative for children to reduce playing with their gadgets; provide children's experiences in problem solving, creativity and collaboration; and include field experience for Polibatam students by applying the knowledge gained through Project Based Learning (PBL) for the benefit of the community.This workshop held four meetings (March to April 2021) at the At-Taqwa Al-Qur'an Education Park (TPA) building, Graha Nusa Batam housing. The robot used is an analog line follower. Pre-test and post-test were conducted to measure the increase in participants' understanding of the material. This test shows that participants' knowledge of robotics technology can increase up to 25% for participants aged 8-11 years and 22% for 12-15 years.